The M&A integration: why M&A in the logistic industry fail to achieve success: an exploratory study of the effects of the integration phase on European logistic firms - Diaz Gomez, Mateo Gonzalo (2016)
The M&A phenomenon has been study for over three decades, yet over this period, there was been modest improvements in M&A success rate. Many scholars estimate that more than 50% of all M&A deals fail to achieve success and many had cited successful integration as key to avoiding the risk of failure. Why so many M&As fail? What are criteria behind achieving a successful integration? Answering those questions encouraged this investigation. The following is an exploratory study of the positive and negative effects of the integration phase on European logistic firms in Belgium, Poland, and The United Kingdom. The study reveals the importance of having a dedicated M&A integration team that can deal with the most common integration issues such as: effective communication, issues with IT platform and its processes, cultural differences, and dealing with the speed of the integration phase.